COMPARISON OF THREE HERBAL PLANTS FOR BEST FREE RADICAL SCAVENGING ACTIVITY - Palaniswamy, Radha; Padma, Palghat Raghunathan (International Journal of Current Pharmaceutical Research, 2017)
Objective: Excessive production of reactive oxygen species leads to oxidative stress. Antioxidants can prevent or retard the oxidation caused by free radicals and sufficient intake of antioxidants is supposed to protect against diseases. Candidate playÂ  Methods: The leaf extracts of these plants were exposed to a battery of free radical scavenging assays like DPPH, ABTS, hydrogen peroxide, superoxide and nitric oxide to determine the free radical scavenging activity. Results: It was observed that the Majoranahortensis leaves in methanolic extract showed maximum scavenging activity. Conclusion: Several plants with free radical scavenging activity have been identified, where Majoranahortensis is one such leave.